Diseño y construcción de una máquina cortadora de envases de vidrio para la producción de vasos a partir de botellas recicladas. - Mendieta Macas, Miguel Andres (2021)
The present job describes a semiautomatic bottler cutter machine, for the productions of recyle cups the micro-company E-glass, now on time makes this process manually. The machine was designed according to the micro-company requirements, getting with the semiautomatic process a production of 240 cups daily. The machine cutting function consist to hold the bottle from the bottom, to create this action we create a concentric holder with three supporters another support keep the bottle in the center and secure. The holder mechanism allow to work with round bottles from 53 mm to 91 mm of diameters and 20 cm to 34 cm longitude. The cutting process is made by a indenter carbide of tusteno, which is held against the bottle while it turns. As a cutting complement a heating system was used in the demarcation for 40 seconds route by means of a nickel that reaches an approximate temperature of 300 degrees Celsius, (°C). The process is developed by semiautomatic, where the operator put and removes the bottle before and after the cut respectively. The process was executed and approved with success, several cutting test were carried out this being the level of quality required by the micro-company E-glass. Keywords: Semi-automatic machine; bottle cutter; cutting process; electromechanical components; recycled glasses.